Relationships of Victimization, Machiavellianism and Conflict Behavior - Viktor P Sheinov (Peoples' Friendship University of Russia (RUDN University), 2018)
The article establishes the mutual links between the victimization, personal Machiavellianism and the conflict-handling modes. Many of these relationships depend on gender and age. A total of 732 subjects participated in the study: 285 women, 110 men, 180 girls and 157 boys. The victimization of subjects was evaluated using the author's test of victimization for adults, Machiavellianism was evaluated with the help of the Mac-IV test, conflict-handling modes was evaluated with the TKI test. Victimization is associated with Machiavellianism, which correlates positively with general victimization, aggressive and uncritical behavior in men, women, boys and girls. In addition, the Machiavellianism in men, women and young men is positively associated with the addictive behavior and with realized victimization, the Machiavellianism of young men and women is associated with self-destructive and non-critical behavior, in young men it is associated with dependent behavior and with realized victimization. The nature of the relationship between victimization and conflict-handling modes is different for the components of victimization and modes. The Competing in men and women, boys and girls is positively associated with general victimization and aggressive behavior. The Accommodating in women and men is negatively correlated with general victimization and aggressive behavior, and in women it is associated with self-destructive and non-critical behavior. The Avoiding in women is negatively correlated with self-destructive and non-critical behavior and with realized victimization, in men it is positively associated with dependent behavior, and in young men it is associated with self-destructive behavior. Compromising in men, women, boys and girls is negatively correlated with general victimization and aggressive behavior. The Collaborating is negatively associated with general victimization and with aggressive behavior in young men and women, and in young men it is also associated with uncritical behavior. The Machiavellianism of men, women and young men is positively associated with Competing and it is negatively associated with Accommodating.